1995
DOI: 10.1111/j.1440-1827.1995.tb03407.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceroid pigment deposition in circulating blood monocytes and T lymphocytes in Hermansky‐Pudlak syndrome: An ultrastructural study

Abstract: An electron microscopic study of peripheral leukocytes obtained from a 39 year old woman with Hermansky-Pudlak syndrome was performed. Ceroid pigment granules were found within the lysosomes in 3.5% of monocytes and 5.4% of lymphocytes. Infrequently, pigment granules were also found in the parallel tubular arrays of lymphocytes. The lymphocytes containing ceroid pigment granules were confirmed to be T cells by immunoelectron microscopy. It was speculated that intralysosomal accumulation of ceroid pigment granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…According to [16] the easy-diffusion paths of Cu + ions in α-Cu 2 Se pass through adjacent 32(f) I and 32(f) II positions in the Fm3m cage, so the occupation of 32(f) intersites by Cu + ions in Li 0.25 Cu 1.75 Se might be considered as an indication of the high mobility of Cu + ions. Large thermal parameters of Cu + ions promote fast ionic diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…According to [16] the easy-diffusion paths of Cu + ions in α-Cu 2 Se pass through adjacent 32(f) I and 32(f) II positions in the Fm3m cage, so the occupation of 32(f) intersites by Cu + ions in Li 0.25 Cu 1.75 Se might be considered as an indication of the high mobility of Cu + ions. Large thermal parameters of Cu + ions promote fast ionic diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…A low energy excitation (LEE) mode has been observed in many cation superionic conductors (SIC) by making use of inelastic neutron scattering experiments [l, 21. Many models of LEE have been proposed till now [2]. However, concerning the origin of LEE, there is no general consensus.…”
Section: Pressure and Temperature Dependences Of The Low Energy Excitmentioning
confidence: 99%
“…The combination of a storage pool deficiency and hypopigmentation places mocha and pearl among the 14 known murine models (Swank et al, 1998) for a human disorder called Hermansky-Pudlak syndrome, or HPS (Hermansky and Pudlak, 1959;Shotelersuk and Gahl, 1998). This autosomal recessive disease consists of oculocutaneous albinism (Witkop et al, 1990;King et al, 1995;Gahl et al, 1998), a platelet storage pool deficiency due to absent dense bodies (Witkop et al, 1987), and accumulation of a lipid-protein complex called ceroid lipofuscin (Sakuma et al, 1995). In 1996, the gene HPS-1 was identified as a cause of HPS (Oh et al, 1996) and subsequently demonstrated to be responsible for the melanocyte dysfunction (Boissy et al, 1998), but the disorder is clearly genetically heterogeneous (Hazelwood et al, 1997;Oh et al, 1998).…”
Section: Introductionmentioning
confidence: 99%